Z kręgu wyobrażeń motywu wstydu w sztuce. Wybrane zagadnienia w sztuce średniowiecznej europejskiej i polskiej - Mazurczak, Urszula (Studia Theologica Varsaviensia, 2017)
Shame is a feeling, it is definable in the areas of psychology, history of culture, and customs in the analyses of the history of religion and ethics. Shame defines the relationship between the object of shame and the subject of this feeling and, ultimately, the subject may not feel ashamed because of an act or a fact, which is not, for him or a certain moral and religious community, understood as a reason for shame. A slightly different, but also related to the concept of ‘shame ‘, is the notion of ‘bashfulness’ understood as a human capability to feel shame to the same extent as the pursuit of other virtues: love, being sensible, faith, chastity, hope, but also humility, modesty and silence. ‘Bashfulness ‘ is an integral part of the condition of a decent, fair and noble life, which in the Roman social education was defined by one common virtue – ‘virtus ‘, known in Greece as ‘arete’. The Christian understanding of virtues and vices, described by Prudentius and later on studied in detail in various texts and works of art by E. Saxl, and A. Katzenellenbogen, specified in detail both virtues and vices at the same time following ancient models. The author undertakes the analysis of the phenomenon of ‘shame’ in the visualisation of Christian, especially medieval, art starting from the accounts of important biblical citations on the ‘shame’ theme. Then she attempts to point out stage images illustrating the religious or moral problem of shame commonly referred to nudity, which, however, is not a proper understanding of shame and bashfulness. The study focuses on selected issues: personification of shame and on the events (described in the Old Testament) which imply shame. The selected images are illustrations of Genesis cycle where the First Parents’ feeling of embarrassment was depicted. The author indicates the sources of ancient compositions of the Aphrodite statue- -Venus Pudica, which developed the topos of ‘shame’ and ‘bashfulness’ imagery. This type of nudity constitutes a distinctive programme of gestures, movement, counterpose and the composition of the head. They are a clear visualisation of the female ideal – of virtues, including the virtue of an ideal love that was associated with bashfulness. The validity of this theme in Italian medieval art, especially in Nicola and Giovanni Pisanos’ works, was pointed out. The personifications of virtues: Venus Pudica or Hercules shown on reliefs in pulpits in Pisa, confirm the validity of the theme of ‘bashfulness’ in medieval art. In the cathedral sculpture, on the outer facades, the sets of virtues and vices used to be depicted, and they were supposed to be addressed to the wide audience of urban publikum. The author of the study pointed out the reliefs of cathedral facades in Paris, Amiens, Magdeburg in which the virtues, including the virtue of shame, had been presented. The columns in the Church of the Norbertine monastery in Strzelno are of great significance for European art. The author also suggested a new iconographic interpretation for the naked figure of Venus pucica. The second field of research is the issue of narrative scenes, the visualisations of nudity based on the Bible, that constitute a positive sense of understanding naked figures in Christian art: Bathsheba in bath, the dancing King David, the suffering Job and the naked, drunken Noah. The author focuses on the analysis of the complex and non-uniformly presented Adam and Eve’s narrative of the feeling of shame. The moments when they experience the feeling of shame and their nudity for the first time are diversified. The author of the Book of Genesis does not mention first parents’ other feelings in paradise, the only statement is the lack of being ashamed of their body at the moment of creation and then the experience of shame after the original sin. The author included more extensive research on the visualisation of the Genesis narrative in her book Human Corporeality in the medieval Italian painting, Vol.I, Lublin 2012. The experience of the first parents’ embarrassment when recognising their nudity was, at the same time, the experience of a permanent virtue of bashfulness. In the Italian series of Genesis imaging the parents experience grace due to the shame they suffered. Additional scenes, which were introduced into cyclical narratives of Genesis and which confirm the meaning of Divine Mercy in the cycle ending the creation of man, are pointed out in the study